CSR (Corporate Social Responsibility) Communication Pattern of Pertamina in Muslim Communities, Rantau District, Aceh Tamiang Regency - Riswanto, Riswanto; Sikumbang, Ahmad Tamrin; Efendi, Erwan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The implementation of CSR communication program is inseparable from the role of public relations as a bridge between Pertamina companies and the community and vice versa. As a resident of Rantau Subdistrict, Aceh Tamiang Regency, Pertamina's CSR has interpersonal and group communication relationships with the community. This research is qualitative research. Qualitative research is social research that fundamentally relies on human observations in its own area and relates to these people who try to reveal the facts/actual phenomena that occur in the field. the actual, the researcher is the key instrument, the data is descriptive, emphasizes the process, the data analysis is inductive, and the meaning of each event is an essential concern in qualitative research. The facts are said because they are in accordance with what is happening on the ground. The purpose of this research is to describe social events, by revealing factual events in the field and revealing hidden values, being more sensitive to descriptive information and trying to maintain the integrity of the object under study. CSR (Corparate Social Responsibility) PT Pertamina communicates partnerships to catfish farms owned by Muslim communities as part of the development of water farms related to the orientation of catfish farming development policies in order to build a prosperous society.